Effect of Soaking Time with Gibberellins on Germination of Sugar Palm Plant Seeds - Rosmaria , Girsang; Ariani Syahfitri , Harahap (Jurnal Online Pertanian Tropik, 2021)
Sugar palm or palm tree (Sugar palm ga pinnata) is a tree that produces industrial materials, almost all parts or products of this plant can be utilized and have economic value. Gibberellin has the advantage of stimulating plant growth, accelerating and stimulating flowering, increasing seedbed yields, accelerating flower ripening, increasing production, accelerating seedling growth, breaking seed dormancy and producing seedless fruit. This study aims to determine the effect of soaking time with gibberellin on the germination of sugar palm plants. The research was conducted on Jl Wonogiri, West Medan District, Medan, starting from January to May 2018. The plant material used is palm plant seeds taken from a natural palm garden in Sipirok This experiment used a factorial randomized block design (RBD) with two treatments, namely immersion time (L0, L1, L2, and L3) and gibberellin (G0, G1, G2, and G3). Data were analyzed using analysis of variance (ANOVA). If the treatment (immersion time, gibberellin concentration and interaction) is significant, then proceed with DMRT (Duncan Multiple Range Test) at Î± = 5%. The observed parameters included: maximum growth potential, germination capacity and apocol length. The results showed that the long immersion treatment with gibberellin had no significant effect on all the parameters of the observation.